2012
DOI: 10.1089/vim.2011.0056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water-Soluble Fraction from Lysozyme-TreatedEnterococcus faecalisFK-23 on Mortality Caused by Influenza A Virus in Mice

Abstract: To maintain homeostasis of the immune system is considered important for the prevention of influenza A virus infection. Aberrant systemic inflammation is frequently induced by influenza A virus infection, and the severity of the symptoms is associated with pathogenicity of the virus. Lactic acid bacteria are known to have a positive effect in maintaining the immune system. Furthermore, preparations of a lactic acid bacteria strain, Enterococcus faecalis FK-23 (FK-23), have been reported to exert preferable hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In this experiment, the LFK dose was fixed at 15 mg per mouse as previous report in which water-soluble fraction of LFK suspension (15 mg per mouse) was administered to mice ( Kondoh et al 2012 ). However, in this experiment, LFK suspension rather than water-soluble fraction of LFK was administered for comprehensive understanding of the mechanism for prevention of influenza by LFK.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this experiment, the LFK dose was fixed at 15 mg per mouse as previous report in which water-soluble fraction of LFK suspension (15 mg per mouse) was administered to mice ( Kondoh et al 2012 ). However, in this experiment, LFK suspension rather than water-soluble fraction of LFK was administered for comprehensive understanding of the mechanism for prevention of influenza by LFK.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that oral administration of the soluble components of LFK, lysozyme-treated lactic acid bacteria E. faecalis FK-23, has an anti-influenza effect by upregulation of the anti-inflammatory cytokine IL-10 in lung ( Kondoh et al 2012 ). However, administration of the LFK suspension did not markedly upregulate IL-10 expression in this study (Figure 3A).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations